Editorial : Women in veterinary epidemiology and economics - Capozzo, Alejandra; Vial, Flavie (Frontiers Media, 2023)
While the number of women graduating from veterinary schools has increased globally over the last few decades, this has not translated into reduced gender bias and inequity in academia and veterinary science research (1). Gender-based discrimination starts at university where women veterinary students are pushed toward “women-majority fields” (e.g., small animal medicine) (2) or where they face discrimination during animal husbandry placements (3). Following graduation, there is clear evidence that gender differences persist in pay and attainment of senior and leadership positions (4). Women's advancement and standing in academic veterinary medicine may in part be influenced by pronounced gender differences in the authorship of veterinary research articles. Women are less likely to be a senior author on a research paper and they are significantly underrepresented in some fields such as surgical and production animal research (5). Gender disparity in professional leadership roles like editorial boards—the median publisher in veterinary sciences had 27.5% editorships belonging to women (6)—can summate by impairing peer recognition and academic advancement.